STUDI LITERATUR: PROSES EVALUASI DALAM SIKLUS PLAN-DO-CHECK-ACTION (PDCA) GUNA MENINGKATKAN KUALITAS PENGAJARAN PENDIDIKAN TINGGI - Muhammad Almaududi Pulungan; Tiara Verita Yastica; Muhammad Nashir Ardiansyah (FORUM PAEDAGOGIK, 2021)
Top Indonesian higher education institution (HEI) has not excelled in education quality in Southeast Asia. The statistics exhibit that only two percent of HEIs comply with requirements of high rank of national accreditation. Lack of management and effective policy of HEIs are the source of low education quality. One of the main reasons is the evaluation, as the basis for decision making, comes from biased measurement. Students, as the consumers in an HEI, are the source of reference for evaluation. Evaluation based on student perspective is important to understand individual learning profiles to formulate policy that meets student needs. This study aims to conduct a preliminary study in understanding the gap in research of higher education quality based on student perspectives that consider systemic approaches such PDCA cycle. We conduct a literature review to map the potential research. The study found five previous studies that conduct quality evaluations involving student perspectives. However, these studies mostly conduct only temporary evaluation, not continuous high frequent measurements. Furthermore, the studies are not supported by an information system which does not lead to a systemic approach. Previous studies may produce biased student evaluation due to the long-time interval between evaluation and schedule of study class. These studies do not take into consideration building a systemic approach of quality evaluation in HEIs. Â Â